Economics of Rainfed Cumin Crop Production in Al-Mukharram District (Journal of Hama University, 2026)
This research aimed to analyze the economics of rainfed cumin production in Al-Mukharram District in the eastern countryside of Homs Governorate for the year 2024. The research relied on primary data collected using a traditional questionnaire that targeted a random sample of farmers, including 100 farmers. The primary data were analyzed using descriptive and quantitative analysis methods through a package of statistical analyses using SPSS and DEAP 2.1 programs, which included the Cobb-Douglas model to estimate the production function, the quadratic model (QCF) to represent the total cost function, and the data envelope method (DEA) to calculate technical production efficiency.The results showed that rainfed cumin cultivation is economically viable, as the economic return per dunum of rainfed cumin production reached approximately 33%, which is considered a good percentage. The net profit margin also reached 24.80%. The production function also showed that fertilizer and pest control were the most prominent inputs that positively affected production, while variable costs showed negative elasticity, which indicates the presence of partial waste in some resources. The data envelope analysis revealed a high average technical efficiency of 98.6%, with a relative superiority for small holdings.The study concluded that improving efficiency requires directing agricultural extension towards the rational use of inputs, especially fertilizers, enhancing the effectiveness of preventive control, and supporting small holdings.
Keywords: : Rainfed cumin, economic return, descriptive and quantitative analysis, Al-Mukharram District